Gaṅgāputra Bhīshma aura Mahābhārata : (mahākāvya) - Bekala, Tārācanda Pāla, 1928- (Naī Dillī : Samaya Prakāśana, 2012)
Epic poem on Bhīṣma, character from Mahābhārata, Sanskrit epic.
Epic poem.
In Hindi.
Keywords: Mahābhārata -- Poetry; Bhīṣma (Hindu mythology) -- Poetry; Mahābhārata.; Bhīṣma -- (Hindu mythological character); Poetry